2016
DOI: 10.1155/2016/7408187
|View full text |Cite
|
Sign up to set email alerts
|

Current Epidemiological Assessment of Bancroftian Filariasis in Tanga Region, Northeastern Tanzania

Abstract: Background. Tanzania started a countrywide lymphatic filariasis elimination programme in 2000 adopting the mass drug administration (MDA) strategy. The drug used for the programme was the combination of ivermectin and albendazole. However, there is limited information on the current epidemiological trend of the infections, where MDA implementation is ongoing. The present study aimed at assessing the current status of Bancroftian filariasis infection rate and morbidity where MDA has been distributed and adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
8
2
Order By: Relevance
“…In Figure 5A, the scrotal enlargements in the younger age group (5-11 years) were not hydrocele, but rather a condition possibly triggered by other conditions, such as congenital inguinal hernias, which are frequently seen in this age group [47], tumors, or tuberculosis. In this age group, hydroceles were not as common as in individuals aged 16-24 years [24,29]. The frequencies of hydrocele observed in this study were similar to those reported in other studies done previously in the study area and elsewhere [18,24].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In Figure 5A, the scrotal enlargements in the younger age group (5-11 years) were not hydrocele, but rather a condition possibly triggered by other conditions, such as congenital inguinal hernias, which are frequently seen in this age group [47], tumors, or tuberculosis. In this age group, hydroceles were not as common as in individuals aged 16-24 years [24,29]. The frequencies of hydrocele observed in this study were similar to those reported in other studies done previously in the study area and elsewhere [18,24].…”
Section: Discussionsupporting
confidence: 90%
“…In this age group, hydroceles were not as common as in individuals aged 16-24 years [24,29]. The frequencies of hydrocele observed in this study were similar to those reported in other studies done previously in the study area and elsewhere [18,24]. High proportions of scrotal swelling, which were not hydrocele, were observed in six study sites (Kichakamiba, Mongavyeru, Tawalani, Maramba A, Mayomboni, and Moa).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…years of annual MDA, such as in Nigeria, Tanzania and Ghana [18][19][20]. In Ghana, after up to 14 rounds of MDA, the transmission of LF still persists in districts with relatively high baseline prevalence [21].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%